Dietary programme impact on biochemical markers in diabetics: systematic review - Barreira, Eduarda (2016)
Given the high prevalence of diabetes in the population and in the elderly, it’s crucial to raise awareness of the need for people to change their eating habits and adopt healthier lifestyles. Nutrition interventions emphasizing the promotion of healthy eating have been shown to be an important point in Diabetes Mellitus treatment since it fosters a better glycaemic control. Objectives: To determine the effectiveness of the implementation of a dietary programme in the amounts of glucose and the lipid profile in patients with Diabetes mellitus. Methods A systematic review of the literature published in 2015 in PubM